Indoor and outdoor navigation based on 3D game engine - Sharkawi, Khairul Hafiz (2007)
GIS expands from simple display to advanced visualization. Today, more and more visualization research were carried out, tested and incorporated with GIS as an effort to realize one of the components in 3D GIS, i.e. 3D navigation. Many navigation systems use 2D maps to represent the real world objects and situations and most of them were not able to provide real information of the situations like shapes, colors and materials of the objects or scenes, as we perceived. Features and navigational landmarks were not easily available for navigating in the real world, as they were very useful and helpful for the navigation purposes. This paper describes an experiment on 3D navigation (indoor and outdoor) within building environment. We utilize a freely available 3D game engine as a navigation tool couple with simple programming effort. We also incorporated the navigation engine with spatial database management system (DBMS). The navigation system works and will be presented. The outlook and future works on the proposed navigation system for 3D GIS will be highlighted.